Regression using hybrid Bayesian networks: Modelling landscape–socioeconomy relationships - Ropero, R F; Aguilera, P A; Fernández, A; Rumí, R (Environmental Modelling & Software, 2014)
Modelling environmental systems becomes a challenge when dealing directly with continuous and discrete data simultaneously. The aim in regression is to give a prediction of a response variable given the value of some feature variables. Multiple linear regression models, commonly used in environmental science, have a number of limitations: (1) all feature variables must be instantiated to obtain a prediction, and (2) the inclusion of categorical variables usually yields more complicated models. Hybrid Bayesian networks are an appropriate approach to solve regression problems without such limitations, and they also provide additional advantages. This methodology is applied to modelling landscape–socioeconomy relationships for different types of data (continuous, discrete or hybrid). Three models relating socioeconomy and landscape are proposed, and two scenarios of socioeconomic change are introduced in each one to obtain a prediction. This proposal can be easily applied to other areas in environmental modelling.
Keywords: Continuous Bayesian networks; landscape; Mixtures of truncated exponentials; Regression; Socioeconomic structure

Linking research to practice: The landscape as the basis for integrating social and ecological perspectives of the rural - Pinto-Correia, T; Kristensen, L (Landscape and Urban Planning, 2013)
The rural spaces in Europe are undergoing complex processes of transition, at multiple scales, and rhythms. In order to grasp and understand the changes occurring, the need emerges for new, con- ceptual approaches that make it possible to combine the different factors that shape spaces. Recent, literature on the multifunctional character of rural spaces and their transition pathways shows the, need for spatially based approaches, where the natural characteristics of a landscape are combined, with the socio-economic and cultural drivers that affect its changes. Experience shows how practical, questions on the changes affecting the rural, addressed by society to the scientific community, are of a, new character and require novel research approaches. This paper argues that landscape based, approaches can be useful basis for the required conceptual innovation. The paper presents and, discusses a set of examples of prac- tice driven research developments, in contrasting regions of Europe. And it proposes a conceptual model which aims to contextualize empirical research driven by, problems set up in practice, and combining the ecological and structural dimensions with the socioeconomic, and cultural ones, all converging in the rural landscape, at multiple scales. The landscape, as, the spatial entity, in its material and immaterial dimensions, is presented in this paper as the most, comprehensive basis for the required step forward. This does not mean a disciplinary landscape, analysis revisited, but a new multi-scale and multi-domain place based approach, where the place is, the rural landscape
Keywords: Conceptual framework; landscape; Post-productivism; Rural paradigms; Transitions

Linking research to practice: The landscape as the basis for integrating social and ecological perspectives of the rural - Pinto-Correia, T.; Kristensen, L. (Landscape and Urban Planning, 2013)
The rural spaces in Europe are undergoing complex processes of transition, at multiple scales, and rhythms. In order to grasp and understand the changes occurring, the need emerges for new, con- ceptual approaches that make it possible to combine the different factors that shape spaces. Recent, literature on the multifunctional character of rural spaces and their transition pathways shows the, need for spatially based approaches, where the natural characteristics of a landscape are combined, with the socio-economic and cultural drivers that affect its changes. Experience shows how practical, questions on the changes affecting the rural, addressed by society to the scientific community, are of a, new character and require novel research approaches. This paper argues that landscape based, approaches can be useful basis for the required conceptual innovation. The paper presents and, discusses a set of examples of prac- tice driven research developments, in contrasting regions of Europe. And it proposes a conceptual model which aims to contextualize empirical research driven by, problems set up in practice, and combining the ecological and structural dimensions with the socioeconomic, and cultural ones, all converging in the rural landscape, at multiple scales. The landscape, as, the spatial entity, in its material and immaterial dimensions, is presented in this paper as the most, comprehensive basis for the required step forward. This does not mean a disciplinary landscape, analysis revisited, but a new multi-scale and multi-domain place based approach, where the place is, the rural landscape
Keywords: Conceptual framework; landscape; Post-productivism; Rural paradigms; Transitions

Dehesas y paisajes adehesados en Castilla y León - Llorente Pinto, J. M. (Polígonos. Revista de Geografía, 2012)
The "dehesas" of Castile and Leon occupy about 5.5% of the regional territory, primarily concentrated in the southwestern sector, the provinces of Salamanca, Avila and Zamora. They show a remarkable variety of lithological substrates, and the Holm oak is the most common tree species in these open woodlands. The farms are large (between 350 and 400 ha on average) and the land tenure is majority ownership. In this farms the livestock is the fundamental production, because it represents just over 75% of income. The dependence on subsidies is now considerable, as with other types of farms. Fattening Iberian pigs and cattle breeding are the main uses, and agricultural and forest uses are subordinate to the grazing. The landscape of this agricultural system is characterized by the prominence of open oak woodland with varying degrees of density. In recent years it has greatly increased the stocking density, and this, coupled with other processes are adversely affecting the internal balance of these agro-ecosystems and their own persistence, primarily because of problems related to a proper state of the trees
Keywords: Castile and Leon; Dehesa; extensive livestock grazing; Forest management; landscape

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development

Conservation of isolated Atlantic heathlands in the Mediterranean region: effects of land-use changes in the Montseny biosphere reserve (Spain) - Bartolomé, Jordi; Plaixats, Josefina; Fanlo, Rosario; Boada, Martí (Biological Conservation, 2005)
In the Mediterranean region, cycles of controlled burning combined with continuous grazing appear to have been an effective tool for maintaining isolated Calluna vulgaris heathlands in the form in which they occur in many places in the Atlantic region. Changes in land use and management of the mosaic of extensively exploited heathland and associated grassland over recent decades, such as bringing land into cultivation followed by its abandonment and the prohibition of fires has resulted in a process of transformation into new shrub communities with lower biodiversity. In the Mediterranean region, these changes are similar to those described in the Atlantic area, but encroachment occurs faster and could lead ultimately to afforestation by Mediterranean woodland.
Keywords: calluna vulgaris; fire; grassland; Grazing; landscape

Conservation of isolated Atlantic heathlands in the Mediterranean region: effects of land-use changes in the Montseny biosphere reserve (Spain) - Bartolomé, Jordi; Plaixats, Josefina; Fanlo, Rosario; Boada, Martí (Biological Conservation, 2005)
In the Mediterranean region, cycles of controlled burning combined with continuous grazing appear to have been an effective tool for maintaining isolated Calluna vulgaris heathlands in the form in which they occur in many places in the Atlantic region. Changes in land use and management of the mosaic of extensively exploited heathland and associated grassland over recent decades, such as bringing land into cultivation followed by its abandonment and the prohibition of fires has resulted in a process of transformation into new shrub communities with lower biodiversity. In the Mediterranean region, these changes are similar to those described in the Atlantic area, but encroachment occurs faster and could lead ultimately to afforestation by Mediterranean woodland.
Keywords: calluna vulgaris; fire; grassland; Grazing; landscape

Estimation of plant diversity at landscape level: a methodological approach applied to three Spanish rural areas - Ortega, M. (Environmental Monitoring and Assessment, 2004)
Approaches linking biodiversity assessment with landscape structure are necessary in the framework of sustainable rural development. The present paper describes a methodology to estimate plant diversity involving landscape structure as a proportional weight associated with different plant communities found in the landscape mosaic. The area occupied by a plant community, its patch number or its spatial distribution of patches are variables that could be expressed in gamma plant diversity of a territory. The methodology applies (1) remote sensing information, to identify land cover and land use types; (2) aspect, to discriminate composition of plant communities in each land cover type; (3) multi-scale ﬁeld techniques, to asses plant diversity; (4) afﬁnity analysis of plant community composition, to validate the stratiﬁed random sampling design and (5) the additive model that partitions gamma diversity into its alpha and beta components. The method was applied to three Spanish rural areas and was able to record 150–260 species per ha. Species richness, Shannon information index and Simpson concentration index were used to measure diversity in each area. The estimation using Shannon diversity index and the product of patch number and patch interspersion as weighting of plant community diversity was found to be the most appropriate method of measuring plant diversity at the landscape level.
Keywords: landscape; Mediterranean vegetation; metrics; plant diversity; Remote sensing

Estimation of plant diversity at landscape level: a methodological approach applied to three Spanish rural areas - Ortega, M (Environmental Monitoring and Assessment, 2004)
Approaches linking biodiversity assessment with landscape structure are necessary in the framework of sustainable rural development. The present paper describes a methodology to estimate plant diversity involving landscape structure as a proportional weight associated with different plant communities found in the landscape mosaic. The area occupied by a plant community, its patch number or its spatial distribution of patches are variables that could be expressed in gamma plant diversity of a territory. The methodology applies (1) remote sensing information, to identify land cover and land use types; (2) aspect, to discriminate composition of plant communities in each land cover type; (3) multi-scale ﬁeld techniques, to asses plant diversity; (4) afﬁnity analysis of plant community composition, to validate the stratiﬁed random sampling design and (5) the additive model that partitions gamma diversity into its alpha and beta components. The method was applied to three Spanish rural areas and was able to record 150–260 species per ha. Species richness, Shannon information index and Simpson concentration index were used to measure diversity in each area. The estimation using Shannon diversity index and the product of patch number and patch interspersion as weighting of plant community diversity was found to be the most appropriate method of measuring plant diversity at the landscape level.
Keywords: landscape; Mediterranean vegetation; metrics; plant diversity; Remote sensing

Multifunctionality in Mediterranean landscapes–past and future - Pinto-Correia, T.; Vos, Willem (The New Dimensions of the European Landscapes, 2004)
During past decades many of the traditional multifunctional Mediterranean landscapes with their typical complexes of agro-, silvo- and pastoral components changed thoroughly. Nowadays only few of them are still vital. Their complex farming systems secure at the same time a multitude of other functions than just agricultural production, such as support for recreation, amenity, cultural identity, preservation of natural resources and environmental quality. Some of these unique, old Mediterranean landscapes are discussed. They cover a broad range from near-tonature high mountain landscapes and terraced small-scale submediterranean polyculture landscapes to dry Mediterranean agro-silvo-pastoral landscapes. All these are changing, either spontaneously due to changing socio-economic and cultural conditions, or as a result of conscious policies, with the Common Agricultural Policy as a main driver. Even measures created to support specific traditional land uses and their landscapes are often not successful as they focus on only a part of the system. These policies and measures will not hold the valuable traditional systems from collapsing and subsequent vanishing. Some other policy instruments, such as those in forestry, are not meant to support them, but to transform them in favour of new monofunctionality. New strategies and instruments ought to deal with these multifunctional landscapes in a more integrated way, if some of them are to be maintained or transformed into others with similar qualities.
The following values have no corresponding Zotero field: periodical: The New Dimensions of the European Landscapes
Keywords: agri-environmental; agro-silvo-pastoral; CAP; landscape; Mediterranean; multifunctionality

Multifunctionality in Mediterranean landscapes–past and future - Pinto-Correia, T; Vos, Willem (The New Dimensions of the European Landscapes, 2004)
During past decades many of the traditional multifunctional Mediterranean landscapes with their typical complexes of agro-, silvo- and pastoral components changed thoroughly. Nowadays only few of them are still vital. Their complex farming systems secure at the same time a multitude of other functions than just agricultural production, such as support for recreation, amenity, cultural identity, preservation of natural resources and environmental quality. Some of these unique, old Mediterranean landscapes are discussed. They cover a broad range from near-tonature high mountain landscapes and terraced small-scale submediterranean polyculture landscapes to dry Mediterranean agro-silvo-pastoral landscapes. All these are changing, either spontaneously due to changing socio-economic and cultural conditions, or as a result of conscious policies, with the Common Agricultural Policy as a main driver. Even measures created to support specific traditional land uses and their landscapes are often not successful as they focus on only a part of the system. These policies and measures will not hold the valuable traditional systems from collapsing and subsequent vanishing. Some other policy instruments, such as those in forestry, are not meant to support them, but to transform them in favour of new monofunctionality. New strategies and instruments ought to deal with these multifunctional landscapes in a more integrated way, if some of them are to be maintained or transformed into others with similar qualities.
Keywords: agri-environmental; agro-silvo-pastoral; CAP; landscape; Mediterranean; multifunctionality

Bird communities of highway verges: Influence of adjacent habitat and roadside management - Meunier, Francis D; Verheyden, Christophe; Jouventin, Pierre (Acta Oecologica, 1999)
We have investigated the effects of landscape traversed and roadside structure on the use of highway verges by birds. Three contrasted landscapes were chosen in terms of human land use and vegetation structure: an intensive farmland, a pine plantation, and a matoral. The roadside sections varied in vegetation structure, width and profile. We recorded birds present in roadsides and adjacent habitats by transect counts over all seasons. Roadside bird species appeared for a great part similar to those of adjacent habitats. However, diversity and abundance in verges did not depend on that of adjacent habitats. Woody roadsides were compararable to hedges, as trees (and shrubs) in verges enhanced species richness and abundance of birds in the farmland and woodland sites. Width and profile of verges had less influence. In all sites, typical species of the habitat traversed partly avoided roadsides. On the contrary, numerous species associated with ‘rare’ habitats in one site preferred roadsides, provided that verge vegetation contrasted with the dominant habitat. It is concluded that birds responses to highways can vary greatly with landscape traversed and verge vegetation. Highway verges could be favorable to birds, if they constitute a complementary habitat to the dominant habitat within a landscape
Keywords: Biodiversity; bird communities; landscape; linear structure; roadside

Contribution to the extensification/intensification debate: new trends in the Portuguese montado - Pinto-Correia, T; Mascarenhas, J (Landscape and Urban Planning, 1999)
The montado is the agro-silvo pastoral system speci®c to the region of Alentejo, Southern Portugal, comprising an open formation of cork and holm oaks in varying densities, combined with a rotation of crops/fallow/pastures. Case studies in different areas of Alentejo, combining the land use and the farmers' decision making, have shown recent extensi®cation in different sub-types of montado. The agro-silvo pastoral system is in transition towards a silvo-pastoral or even purely forestry system. Cultivation is becoming less important in the system rotation, whereas livestock production is becoming more relevant and the ground cover is used only as pasture. The cork is still valuable and, in most cases, is the ®rst priority in the exploitation. New alternative uses are arising; they include hunting and rural tourism, both intended to support the preservation of the traditional landscapes. All these uses are supported directly or indirectly by the EU's CAP; for example, through agro-environmental measures. Although scrub patches are becoming larger, complete land abandonment is rare. These land use systems are based on a use that is even more extensive. Consequently the landscape is changing, but a new equilibrium, displaying new land cover mosaics, might be attained. Concomitantly, intensi®cation is occurring in certain areas. It causes degradation as a result of various management factors: (a) harvesting activity and deep ploughing in the areas where crops are cultivated, (b) too high stocking rates in relation to the carrying capacity of the system, impeding, for example, the natural regeneration of the tree cover; (c) introduction of heavy cattle breeds, which aggravates the problem of overstocking and results in direct damage to the soil structure and to the tree root system. The clearing of the shrub layer with heavy machinery affects the Quercus regeneration in both extensively and intensively managed patches, but no effective alternatives have yet been found. Today, the main landscape problem of the montado is not the abandonment of the system due to extensi®cation, but is rather: (1) whether the current extensi®cation is leading to a new equilibrium in an extensive silvo-pastoral or merely forestry system, and what type of landscape mosaic this change is creating; and (2) whether it is possible to avoid short-term intensi®cation and improve mechanisation to clear shrubs without degradation; (3) to what extent these changes depend on the CAP and how they will react to CAP changes in the future.
Keywords: extensification; intensification; land use; landscape; montado

A landscape in transition: an historical perspective on a Spanish latifundist farm - Pérez, A S; Remmers, G G A (Agriculture, ecosystems & environment, 1997)
An agricultural landscape, as a social construction, is not static, but a reflection of the balance of social forces which influence the way in which the natural resources of the site are combined. To understand and evaluate the current configuration of a landscape, and to define and understand criteria according to which a future landscape may be designed, it is necessary to analyse its historical construction. In this paper we follow these steps, taking as a point of reference a farm in one of the most important agricultural regions of Spain, the Guadalquivir river valley in Andalucla. This region stands out for its high production potential, social inequity and environmental degradation. The paper describes global changes in the use of the land in this river valley over the past 3 centuries, and uses aerial photographs from 1956 and 1990 to outline changes on the 1150-ha Los Humosos farm, recently granted to a co-operative of land labourers after years of struggle for land. Through this change in tenure the criteria 'control' and 'distribution of benefits' are achieved. Nine other criteria derived from the historical analysis were used to compare four different farm design scenarios through multi-criteria programming, which was preceded by an assessment of the biogeophysical characteristics of the land. However, this appeared to be insufficient to cope with essential criteria such as landscape architecture and biodiversity, because minor landscape elements were neglected which are important starters for the design of an ecological infrastructure. Water, a problematic resource in Mediterranean agriculture, paradoxically turned out to be an important characteristic of these landscape elements. From historical, ecological and social perspectives, new proposals for farm landscape design must necessarily and radically break with the recent past. It appears, however, that to produce agricultural landscapes of quality in the Guadalquivir river valley would involve tough social struggle, that nonetheless is found to use the margins left over by the dominant socio-economic, cultural and political structures. Finally, an agro-ecological option is proposed as a transitional design
Keywords: ecological agriculture; History; land labourers; landscape; Mediterranean; Spain; water

Threatened landscape in Alentejo, Portugal: the 'montado'and other 'agro-silvo-pastoral'systems - Correia, T. P. (Landscape and Urban Planning, 1993)
In Portugal agro-silvo-pastoral systems correspond to the mixed land use types characteristic of the region of Alentejo, in the southern part of the country. There is a triple and complementary use of the land, adapted to the low potentialities of the soil and to the Mediterranean climate: open evergreen forest (oaks, olive and chestnut trees), grazing and cultivation. Due to their mixed characteristics and to the extensive form of exploitation, these systems constitute varied landscapes of high biological diversity. They have been managed through decades as an almost self-maintained system, with a minimum of human work input, but furnishing nevertheless the necessary outputs for the dispersed rural population of the area. Actually, due to the decrease in the economic value of some of the products concerned and to the changing context for Portuguese agriculture, these agro-silvo-pastoral systems have registered perturbations by intensification or extensification; in both cases there is a degradation or disappearance of the corresponding landscapes.
Keywords: land use (voyant); landscape; montado

Threatened landscape in Alentejo, Portugal: the 'montado'and other 'agro-silvo-pastoral'systems - Correia, T P (Landscape and Urban Planning, 1993)
In Portugal agro-silvo-pastoral systems correspond to the mixed land use types characteristic of the region of Alentejo, in the southern part of the country. There is a triple and complementary use of the land, adapted to the low potentialities of the soil and to the Mediterranean climate: open evergreen forest (oaks, olive and chestnut trees), grazing and cultivation. Due to their mixed characteristics and to the extensive form of exploitation, these systems constitute varied landscapes of high biological diversity. They have been managed through decades as an almost self-maintained system, with a minimum of human work input, but furnishing nevertheless the necessary outputs for the dispersed rural population of the area. Actually, due to the decrease in the economic value of some of the products concerned and to the changing context for Portuguese agriculture, these agro-silvo-pastoral systems have registered perturbations by intensification or extensification; in both cases there is a degradation or disappearance of the corresponding landscapes.
Keywords: land use (voyant); landscape; montado

Land abandonment : Changes in the land use patterns around the Mediterranean basin - Correia, T Pinto (Options Méditerranéennes, 1990)
This paper focuses on land abandonmenitn the EEC Mediterranean regions, where the phenomenon, in its actual extension and its trends towards aggravation, demands urgent monitoring and management. The causes and processes of land abandonment are analyzed, as well as the consequences at landscape and ecological level. Depending also on the socio-economic context, new strategies for land management are outlined.
Keywords: extensification; Land abandonment; landscape; marginalization; Mediterranean